IGF2BP3 May Contributes to Lung Tumorigenesis by Regulating the Alternative Splicing of PKM - Xueqing, Huang; Jun, Zhang; Yueqiang, Jiang; Xin, Liao; Liya, Hu; Yuanyuan, Fang; Yuting, Zhang; Hao, Zeng; Hua, Wu; Jian, Liu; Tiejun, Yin (Frontiers in Bioengineering and Biotechnology, 2020)
RNA binding proteins (RBPs) play a key role in genome regulation. Here we report the post-transcript regulation of IGF2BP3, which belongs to the insulin-like growth factor 2 mRNA binding protein family. We used iRIP-seq and RNA-seq to analyze the transcript regulation and alternative splicing induced by IGF2BP3 overexpression. As a result, the overexpression of IGF2BP3 has broadly up-regulated the expression of genes involving in G-protein coupled receptor signaling pathway, positive regulation of cell proliferation and signal transduction. In addition, IGF2BP3 regulated the alternative splicing of multiple genes associated with response to hypoxia, negative regulation of transcription, and embryonic development. To our best knowledge, this is the first study to examine the down-stream transcripts and alternative splicing of IGF2BP3, which laid the foundation for later research on the critical functions of IGF2BP3.